PENGEMBANGAN MEDIA VIDEO ANIMASI DALAM MATERI KEDATANGAN BANGSA EROPA KE NUSANTARA PADA PEMBELAJARAN IPAS KELAS VI DI SEKOLAH DASAR - Rahmatillah, Putri; Aprilia, Rapita; Juliati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study was motivated by the limited use of innovative learning media in teaching the topic of the Arrival of European Nations in the Indonesian Archipelago, resulting in learning activities that were predominantly conducted through lectures and textbooks. This condition caused students to experience difficulties in understanding historical concepts that are abstract in nature, participate less actively in the learning process, and achieve suboptimal learning outcomes. This study aimed to develop an animated video learning media that is valid, practical, and effective for teaching the topic of the Arrival of European Nations in the Indonesian Archipelago in Grade VI IPAS (Science and Social Studies) learning at SD Negeri Paya Pelawi. This study employed a Research and Development (R&D) approach using the ADDIE model. The research instruments included material expert validation sheets, language expert validation sheets, media expert validation sheets, teaching module validation sheets, pretest–posttest instrument validation sheets, teacher and student response questionnaires, and learning achievement tests. The results showed that the animated video learning media achieved a very high level of validity, with material expert validation reaching 96%, language expert validation 96%, media expert validation 77% (feasible), teaching module validation 95%, and pretest–posttest instrument validation 95%. The practicality level reached 92% in the small-group trial, 92% in the large-group trial, and 90% based on the teacher's response, all of which were categorized as highly practical. The effectiveness of the learning media was demonstrated by an increase in students' learning mastery from 40% in the pretest to 75% in the posttest. Therefore, the developed animated video learning media was found to be valid, practical, and effective, making it suitable for use as an alternative learning medium in Grade VI IPAS learning on the topic of the Arrival of European Nations in the Indonesian Archipelago at the elementary school level.